Neuropsychological Test Performance in Cognitively Normal Spanish-speaking Nonagenarians with Little Education - Guerrero Berroa, Elizabeth (2016)
To find associations of age, sex, and education with neuropsychological test performance in cognitively normal Spanish-speaking Costa Rican nonagenarians with little education; to provide norms; and to compare their performance with similar Puerto Ricans. For 95 Costa Ricans (90–102 years old, 0–6 years of education), multiple regression assessed associations with demographics of performance on six neuropsychological tests. Analyses of covariance compared them with 23 Puerto Ricans (90–99 years old). Younger age and being female—but not education—were associated with better performance on some neuropsychological tests, in particular episodic memory. The Puerto Ricans performed better on learning and memory tasks. In cognitively intact Spanish-speaking nonagenarians with little or no education, education did not affect test performance. Additional studies of the effect of education on cognitive performance are warranted in other samples with extremely low education or old age. National differences in performance highlight the importance of group-specific norms.